Inovasi teknologi hidroponik melalui pemanfaatan barang bekas dan nutrisi buatan sendiri sebagai usaha peningkatan pendapatan petani di Desa Kualu Kecamatan Tambang Kabupaten Kampar - Fitmawati Fitmawati; Mayta Novaliza Isda; Isnaini Isnaini; Nery Sofiyanti; Rodesia Mustika Roza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The hydroponic technology of the wick system is one of the innovations in vegetable cultivation without soil with the innovation of utilizing used goods and household waste such as styrofoam and used cans as a container for planting. The purpose of this activity is to reduce waste in the community, improve the family's economic capacity, and people's interest in consuming clean and hygienic vegetables in Kualu Village, Tambang District, Kampar Regency. This hydroponic technique is made of relatively inexpensive and affordable materials so that the limitations of people's financial capabilities can be overcome. This system is a hydroponic system that uses axes to absorb organic nutrients. To minimize the cost of purchasing nutrients, it can be overcome by innovating nutrient solutions from household waste into liquid fertilizer. The implementation of community service uses counselling, discussion and making hydroponic technology. The community is very enthusiastic in joining this program, especially housewives who want to know the application of Wick's hydroponic technology so that they can play a large role in meeting food needs and increasing people's income.